PENGEMBANGAN INFRASTRUKTUR WILAYAH SEBAGAI UPAYA PENINGKATAN PERTUMBUHAN EKONOMI DAN PELAYANAN DASAR DI KABUPATEN CILACAP - Kristian Cahyandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
To support increased economic growth and basic services to the community, the quality of infrastructure in each region must be developed such as transportation, education, health, electricity and residential infrastructure. Provision of infrastructure is also very necessary in order to support the implementation of various economic and social activities in the community. The data used in this study are secondary data consisting of BPS data in Cilacap Regency and BPS in Central Java Province 2018, Journals and research related to research. The analytical method used is Klassen Tipology and Estimated Ratio Model (MRP). The results of this study indicate that to improve economic growth and basic services, it is necessary to strengthen connectivity through increased procurement of roads and bridges to connect production areas with distribution areas and facilitate access to tourism areas and increase transportation infrastructure by supporting districts as suppliers of various basic needs for growth and regional and national development.